2017
DOI: 10.21608/agro.2017.499.1051
|View full text |Cite
|
Sign up to set email alerts
|

Boron’s Importance in Plant Development and Growth: A review

Abstract: Interdict of hydrogen ion deliver due to boron draw up and amends in plant substrate demonstrated boron association in cell wall actions it's a unique micronutrient depends for common plant growth and optimum yield of crops. Its concentration in soil and plant not only varies with soil, plant, but also its overdose or defect, may affect the plant growth and production. Boron in soils gradually influence by several factors among of its, soil pH, organic matter, nutrient interactions, and plant species. Deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…1). The FTIR spectroscopy of borate containing compounds has vibrational modes mainly active in three infrared spectral regions (i) 1600-1200 cm -1 group of bands which are due to the asymmetric stretching relaxation of B-O bond of trigonal BO3 units (ii) bands in the range 1200-800 cm -1 due to B-O bond stretching of tetrahedral BO4 units and (iii) peaks around 700 cm -1 due to bending of B-O-B linkages in the borate networks [3]. The bands in the range 3600-3200 cm -1 are attributed to the hydroxyl or water groups originating from molecular water [4].…”
Section: Resultsmentioning
confidence: 99%
“…1). The FTIR spectroscopy of borate containing compounds has vibrational modes mainly active in three infrared spectral regions (i) 1600-1200 cm -1 group of bands which are due to the asymmetric stretching relaxation of B-O bond of trigonal BO3 units (ii) bands in the range 1200-800 cm -1 due to B-O bond stretching of tetrahedral BO4 units and (iii) peaks around 700 cm -1 due to bending of B-O-B linkages in the borate networks [3]. The bands in the range 3600-3200 cm -1 are attributed to the hydroxyl or water groups originating from molecular water [4].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the amount of Sulphur required to produce one ton of seed is about 3-4 kg Sulphur for cereals; 8 kg Sulphur for legume crops; and 12 kg Sulphur for oil crops. (Abou Seeda et al, 2020). Majority of the crops cultivated in Gaya and Wudil farms are sorghum, millet and cowpea with few vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Most metals do not undergo microbial or chemical degradation (Kirpichtchikova et al, 2012), and their total concentration in soils persists for a long time after their introduction (Adriano et al, 2003). Heavy metal soil csontamination can present risks and dangers to animals and the ecosystem through immediate intake or contact with contaminated soil, food chain, soil-contaminated water drinking, and food quality decrease (McLaughlin et al, 2001;Ling et al, 2007); Abou seeda et al, 1997 andAbou Seeda et al, 2019) reported that major frequent contaminants in soil are heavy metals that may be responsible for detrimental health effects.…”
Section: Introductionmentioning
confidence: 99%